2017
DOI: 10.1038/s41598-017-15935-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient increases in intracellular calcium and reactive oxygen species levels in TCam-2 cells exposed to microgravity

Abstract: The effects of microgravity on functions of the human body are well described, including alterations in the male and female reproductive systems. In the present study, TCam-2 cells, which are considered a good model of mitotically active male germ cells, were used to investigate intracellular signalling and cell metabolism during exposure to simulated microgravity, a condition that affects cell shape and cytoskeletal architecture. After a 24 hour exposure to simulated microgravity, TCam-2 cells showed 1) a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 57 publications
(44 reference statements)
2
47
0
Order By: Relevance
“…Lactate levels in growth media of PGL cells treated and untreated with DCA were measured as previously described 47 . Briefly, cells were seeded in 12-well plates (1 × 10 5 cells/well) and, following cell attachment, they were treated for 24 hours with 50 mM DCA, or with vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Lactate levels in growth media of PGL cells treated and untreated with DCA were measured as previously described 47 . Briefly, cells were seeded in 12-well plates (1 × 10 5 cells/well) and, following cell attachment, they were treated for 24 hours with 50 mM DCA, or with vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Neuronal NOS (nNOS) is constitutively expressed in neuronal tissue, and the endothelial NOS (eNOS) is mostly expressed in endothelial cells. Both are constantly active in response to stimuli, such as oxidative stress, that induce an increase in the intracellular Ca 2+ concentration [104]. Inducible NOS (iNOS) is found in macrophages, neutrophils, microgial, and astroglial cells and is expressed in response to different factors such as cytokines and bacterial lipopolysaccharide [105].…”
Section: Tissue-specificmentioning
confidence: 99%
“…In addition, there is the possibility that the higher intensity of UV radiation, which is a driving force of evolution, and the complex cosmic IR in space could lead to an increase in the mutation frequency. Currently, μG has been reported to cause cellular oxidative stress that leads to production of ROS and endoplasmic reticulum stress in experimental animals [196][197][198]. In addition, Sugimoto et al reported that the environment during spaceflight induces oxidative stress and ROS gene network activation in the space-grown Mizuna plant [199].…”
Section: Combined Effects Of μG and Uv Radiation On Plantsmentioning
confidence: 99%
“…The mechanisms by which μG elicits these cellular responses remain poorly understood, although very interesting results have been reported recently. For example, simulated μG induces autophagy via mitochondrial dysfunction in human Hodgkin's lymphoma cells [196] and TCam-2 cells [197]. The results of proteomic and metabolomics analysis of human primary osteoblasts exposed to simulated μG suggest that μG suppresses bone cell function, impairing mitochondrial energy potential and the energy state of the cell [200].…”
Section: Combined Effects Of μG and Uv Radiation On Plantsmentioning
confidence: 99%